The composer phenomenon in a historical retrospect of an authorship idea formation in European musical culture of the middle ages - Konovalova, Iryna Yu (Linguistics and Culture Review, 2021)
The article is devoted to comprehension of specifics and formation prerequisites of composer’s and musical authorship phenomena historical formation in European culture of the Middle Ages. Genesis of composer’s phenomenon and individual musical authorship model is considered on the basis of historical, socio-cultural and aesthetic-artistic transformations, on awareness about their dynamic’s tendencies and general cultural institutionalization of an authorship phenomenon, as well as on an increasing role of individual creativity in an artistic realm. It is stated that multi-ethnic and anonymous culture of oral tradition, folklore and Christian singing practices, as well as instrumental improvisation’s traditions, became spiritual sources of this phenomena and turn into a strong foundation of musical professionalism and creative impulse for European authorial music evolution. It is emphasized that process of composer’s formation as a creativity subject and musical professionalism carrier was stimulated by the necessity of everyday vocal-choral practice, conditioned by the spiritual context of time, by intention on theocentric world’s picture and religious – Christian outlook dominance. Significant role of secular direction development in the context of music-author’s discourse formation and composer’s figure assertion in the late Middle Ages is highlighted.